Prevalence of human immunodeficiency virus infection among primigravida, in Karnataka - Srinivas, Vani; Prasad, T. L. N.; Patil, Rajesh T.; Khaparde, Sunil D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Karnataka is one of the six high human immunodeficiency virus (HIV) prevalent states in India. We estimated prevalence among primigravida attending antenatal clinics in Karnataka, assuming this as a proxy for HIV incidence level in the general population. Methods: We tried estimating prevalence among primigravida using cross sectional samples. Data was collected in structured data extraction sheet for the month of September 2011, from all Integrated and Counselling tested Centres (ICTCs) of Karnataka. All the pregnant women were tested as per national protocol. We analysed the basic demographic data, geographical distribution including HIV status of spouse of primigravida. Results: In September 2011, 87580, pregnant women were tested and 238 (0.26%) were found HIV positive of which, 95 (40%) were primigravida. Prevalence among primigravida, was 0.3%. The prevalence among primigravida was highest in Bagalkot (1.6%) district. In Yadgir, Kodagu and Udupi the prevalence was zero. The high prevalent blocks were Jamakhandi, Mudhol, Gokak, Hospet and Muddebihal. 73.7% spouse of positive primigravida were tested for HIV and among those tested, 87.1% were found HIV positive. Conclusions: There is striking difference in the prevalence of HIV among primigravida in different districts of Karnataka probably indicates the difference in effectiveness of preventive interventions in these districts and within blocks. The preventive programs should be reached out to the labourer’s and farmers in the general population to prevent the new infections in the general population.